Sosialisasi dan Pendampingan Perencanaan Tempat Pembuangan Sementara di Desa Wisata Pinge Kabupaten Tabanan - Singgih Sasongko; Ni Made Prasiwi Bestari; I Nyoman Indra Kumara (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
The useful value of objects that have been used up can be called trash. Decreasing the use value of objects can occur due to human activities, animal activities, and natural events. Waste if not managed with a good system can cause environmental problems. This environmental problem is currently happening in Pinge Tourism Village, Tabanan Regency. Pinge Tourism Village is developing into an international-standard tourist village, so education and planning are needed in waste management to solve ongoing environmental problems. Education and planning for the provision of Reduce-Reuse-Recycle Temporary Disposal Sites (TPS 3R) can be a solution in solving environmental problems in Pinge Village. Collecting data through interviews with village officials, direct observation in the village, and conducting literature studies to determine methods for determining solutions to environmental problems in Pinge Village. The results of the waste processing system with TPS 3R are such as recycling and compost waste, but the main goal of TPS 3R is to reduce waste piles and simplify the waste disposal process before going to the final disposal site. The design of TPS 3R in Pinge Village is adjusted to the standards and existing conditions of the land, so that it requires land with an area of 80 m2 with several rooms that have their respective functions so that they can support the operation and mechanism of waste segregation